Biomechanical factors associated with tibial stress fracture in female runners - Milner, C. E.; Ferber, R.; Pollard, C. D.; Hamill, J.; Davis, I. S. (Medicine & Science in Sports & Exercise, 2006)
Purpose: Tibial stress fractures (TSF) are among the most serious running injuries, typically requiring 6-8 wk for recovery. This cross-sectional study was conducted to determine whether differences in structure and running mechanics exist between trained distance runners with a history of prior TSF and those who have never sustained a fracture.